Respuesta :
Answer:
(a) [tex]L=-\infty[/tex]
(b) [tex]L=\text{Indeterminate}[/tex]
(c) [tex]L=\infty[/tex]
Step-by-step explanation:
We are given,
[tex]\lim_{x\rightarrow a}f(x)=0[/tex]
[tex]\lim_{x\rightarrow a}g(x)=0[/tex]
[tex]\lim_{x\rightarrow a}h(x)=1[/tex]
[tex]\lim_{x\rightarrow a}p(x)=\infty[/tex]
[tex]\lim_{x\rightarrow a}q(x)=\infty[/tex]
Evaluate the limit:
(a) [tex]L=\lim_{x\rightarrow a}[f(x)-p(x)][/tex]
Using limit property, Distribute the limit
[tex]L=\lim_{x\rightarrow a}f(x)-\lim_{x\rightarrow a}p(x)][/tex]
[tex]L=0-\infty[/tex]
[tex]L=-\infty[/tex]
(b) [tex]L=\lim_{x\rightarrow a}[p(x)-q(x)][/tex]
Using limit property, Distribute the limit
[tex]L=\lim_{x\rightarrow a}p(x)-\lim_{x\rightarrow a}q(x)][/tex]
[tex]L=\infty-\infty[/tex]
[tex]L=\text{Indeterminate}[/tex]
Because difference of two infinity might be finite or infinite.
(c) [tex]L=\lim_{x\rightarrow a}[p(x)+q(x)][/tex]
Using limit property, Distribute the limit
[tex]L=\lim_{x\rightarrow a}p(x)+\lim_{x\rightarrow a}q(x)][/tex]
[tex]L=\infty+\infty[/tex]
[tex]L=\infty[/tex]
Using limit properties, it is found that:
a) [tex]\lim_{x \rightarrow a} [f(x) - p(x)] = -\infty[/tex]
b) Undetermined.
c) [tex]\lim_{x \rightarrow a} [p(x) + q(x)] = \infty[/tex]
In this problem, the property considered is:
- The limits of the sum/subtraction is the sum/subtraction of the limits.
Item a:
[tex]\lim_{x \rightarrow a} [f(x) - p(x)] = \lim_{x \rightarrow a} f(x) - \lim_{x \rightarrow a} p(x) = 0 - \infty = -\infty[/tex]
Item b:
[tex]\lim_{x \rightarrow a} [p(x) - q(x)] = \lim_{x \rightarrow a} p(x) - \lim_{x \rightarrow a} q(x) = \infty - \infty[/tex]
Then undetermined.
Item c:
[tex]\lim_{x \rightarrow a} [p(x) + q(x)] = \lim_{x \rightarrow a} p(x) + \lim_{x \rightarrow a} q(x) = \infty + \infty = \infty[/tex]
A similar problem is given at https://brainly.com/question/16553497